2021
DOI: 10.1002/adma.202100012
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Cytokines with Advanced Materials: A Potential Strategy to Tackle COVID‐19 Cytokine Storm

Abstract: as 2019-nCoV), [1] has caused more than 83 million infections and 1.8 million deaths globally as of January 1, 2021. [2] In the past 200 years, multiple epidemics induced by emerging viruses, such as SARS-CoV, Zika virus, Ebola virus, and recently SARS-CoV-2, have posed unprecedented threats to global public health. [3] Although several vaccine candidates have been approved by the U.S. Food and Drug Administration (FDA) for emergency prevention of SARS-CoV-2 infection, so far there is still absence of effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 100 publications
(209 reference statements)
0
36
0
Order By: Relevance
“…Some therapies aimed at countering or neutralizing a single cytokine ( e.g. , IL-6 or TNF-α blockers) have been developed and have shown certain beneficial effects in preclinical models [ 7 , 8 ], but they have shown controversial results in clinical trials of COVID-19 treatment [ 9 ]. The possible reason is that single cytokine-targeted therapy may function well when this cytokine is the driving factor in this disease, while the mechanisms of cytokine storms are complicated, and many cytokines are involved [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some therapies aimed at countering or neutralizing a single cytokine ( e.g. , IL-6 or TNF-α blockers) have been developed and have shown certain beneficial effects in preclinical models [ 7 , 8 ], but they have shown controversial results in clinical trials of COVID-19 treatment [ 9 ]. The possible reason is that single cytokine-targeted therapy may function well when this cytokine is the driving factor in this disease, while the mechanisms of cytokine storms are complicated, and many cytokines are involved [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A cytokine storm is characteristic of COVID-19. 26 Significant release of proinflammatory cytokines and changes in the number and function of lymphocytes are related symptoms. 27 We found that the percentage of CD8+ T cells in the first blood test (T1) was a risk factor for stage T3 liver dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The non-specific biodistribution in vivo and dose-limited side effects further limit the wide application of these free antibodies. The latest developments in biomaterials and nanotechnology ( 85 ) provide many promising opportunities for infectious and inflammatory diseases.Recently, the team of Rao ( 86 ) and other researchers proposed new biomaterials in improving the role of antibody and broad spectrum cytokines. This multi-functional neutralization platform ( 87 ) can solve the problem of multiple cytokines released in different diseases at the same time, which is conducive to the development.…”
Section: Discussionmentioning
confidence: 99%